Development and characterization of a new colorimetric based time–temperature indicator - Sucheta, Tarun (My University, 2019)
Food and consumer safety is primary objective of any food industry; hence to achieve this important objective, food quality as well as food and consumer safety should be maintained from production to final consumption where food spoilage is controlled. Food spoilage is the result of combine effect of two crucial factors i.e., time and temperature. The visible color changing time temperature indicator (TTIs) are usually monitoring the food spoilage by the correlation of activation energy (Ea) of both TTI and food spoilage parameters. The characterization of color changing TTI strip where the concentration of TTI substrate i.e., lactic acid and activation energy (Ea) of the color response (from pink to yellow) are addressed. The activation energy of each developed TTI strip was calculated by plotting an Arrhenius curve between 1/T where T is absolute temperature and ln k. The correlation coefficient of determination R2 and activation energy (Ea) of each TTI are described. Among all TTI developed, five TTIs showing the higher coefficient of determination R2 as well as activation energy ranged from 25.64 to 121.48 KJ/mol that can be suitable for various range of food products. The developed TTI can be used for chicken meat and ground beef as the previous studies reported that the activation energy values of ground beef, cooked chicken meat as well as raw chicken meat are ranged between 84 KJ/mol to 115 KJ/mol. Chicken meat spoilage analysis was performed by considering the TVB (Total viable bacteria counts) and TVB-N (Total volatile base nitrogen). The activation energies of the TVB-N production and TVB level during the storage of chicken meat were 44.29 KJ/mol to 63.74 KJ/mol. The MATLAB curve fit tool (*cftool*) was used to apply different linear and nonlinear regression models. Based on the individual model summary, the correlation coefficient of determination R2 and %RMSE were selected for the optimization of the regression model as least %RMSE and higher R2 value show the goodness of fit for the particular regression model. The derived activation energy can be considered as targeted activation energy and applied in the regression model to acquire the concentration of TTI substrate for the developed TTI strip. By the regression model, the TTI substrate concentration was calculated, i.e., 0.45M. Therefore, 8μl of 0.45 M lactic acid was used as an activation substrate of the developed TTI strip and employed on the chicken packet for real-time monitoring of the chicken meat spoilage.
Keywords: Time temperature indicator; Lactic acid; activation energy; TTI strip